Building a rural medical workforce: the foundations of a place-based approach to program evaluation - Lara Fuller; Jessica Beattie; Vincent L. Versace; Gary D. Rogers; Matthew Richard McGrail (Frontiers in Medicine)
IntroductionTo address the maldistribution of medical practitioners within Deakin University’s rural training footprint, a place-based Rural Training Stream (RTS) was established (2022). Formal definition of the footprint has enabled priority admission of 30 local students annually. This paper describes graduate workforce outcomes for the footprint, providing a baseline for future evaluation of the RTS.MethodsGraduates’ (2011–2022) Principal Places of Practice (2023) were extracted from the Australian Health Practitioner Regulation Agency register and linked with demographic, admission and training data. Descriptive statistics, univariate analysis and multinomial logistic regression were employed to describe associations with practice in three defined rural Tiers (Tier 1: Deakin’s rural footprint, Tier 2: other rural Victoria, Tier 3: other rural Australia), with metropolitan practice as the reference group.Results120 (39.2%) graduates were working in Tier 1 and 93 (30.4%) in each of Tiers 2 and 3. Significant associations (p < 0.001) with working in the footprint were: post-graduate years 1–3 (OR 7.2), rural longitudinal integrated clerkship and rural clinical school (RCS) pathway (OR 6.8); RCS pathway only (OR 4.1), general practice specialty (OR 4.7) and rural background (OR 3.0).DiscussionThe differential effect of rural training on graduates working in the rural footprint, compared with other parts of rural Victoria and Australia is noteworthy. Attrition of graduates from the footprint beyond post-graduate year three highlights the urgency of expanding rural specialty training pathways. These baseline data reinforce the place-based design of the RTS and provide a foundation for future evaluation of local workforce outcomes.